Cell Phone Nation
The cheap mobile phone is probably the most disruptivecommunications device in history, and in India its potential tostir up society is breath-taking. The number of phones in Indiaincreased more than twenty times in the last ten years, and by theend of 2012 India had more than 900 million mobile phonesubscribers. The impact of the simplest version of the device hasbeen deep. Village councils have banned unmarried girls from owningmobile phones. Families have debated whether new brides shouldsurrender them. Cheap mobiles have become photo albums, musicmachines, databases, radios and flashlights. Religious images anduplifting messages continue to flood tens of millions of phoneseach day. Pornographers and criminals have found a tantalizing newtool. Political organizations have exploited a resource infinitelymore effective than the printing press for carrying messages toworkers, followers and voters. Cell Phone Nation masterfully probesthe mobile phone universe in Indiafrom the contests of great capitalists and governments tocontrol Radio Frequency spectrum to the ways ordinary people buildthe troublesome, addictive device into their daily lives.